Valle, J. M. & Núñez, J. A. (Eds.).(2016). Educación, supranacionalidad y ciudadanía. Madrid: Fundación Santillana. ISBN-978-84-680-4078-3 - Alonso Sainz, Tania (Journal of Supranational Policies of Education (JOSPOE), 2016)
Valle, J. M. & Núñez, J. A. (Eds.).(2016). Educación, supranacionalidad y ciudadanía. Madrid: Fundación Santillana. ISBN-978-84-680-4078-3